Predictive Value Analysis of Serum sFlt-1 and PLGF Levels/Ratio in Preeclampsia - Shuyuan Xue; Ying Feng; Wei Li; Guifeng Ding (IMR Press, 2022)
Background: This study is to explore the clinical significance of serum sFlt-1, and placental growth factor (PLGF) contents, as well as sFlt-1/PLGF ratio in predicting and diagnosing preeclampsia. Methods: Peripheral venous blood was collected from all pregnant women at 11-33+6 weeks for biomarker detection. Totally 105 patients with preeclampsia and 57 patients with severe preeclampsia were included. Serum sFlt-1 and PLGF levels were determined, and sFlt-1/PLGF ratio was calculated. Correlation between sFlt-1, PLGF, sFlt-1/PLGF ratio and serum total cholesterol, triglyceride, lactate dehydrogenase and calcium content levels were analyzed. receiver operating characteristic (ROC) analysis was used to evaluate values of sFlt-1, PLGF and sFlt-1/PLGF ratios in disease diagnosis and prediction. Results: Serum sFlt-1 content and sFlt-1/PLGF ratio in Preeclampsia (PE) patients were significantly higher than control. Serum sFlt-1 content and sFlt-1/PLGF ratio of the severe PE group were significantly higher than the PE group. Serum PLGF contents of the PE and severe PE group were significantly lower than control, and the difference in PLGF content between the severe and PE groups was not significant. There was a moderate correlation between the sFlt-1 content and the lactate dehydrogenase level. There was a low-level correlation between the sFlt-1/PLGF ratio and the lactate dehydrogenase level. The receiver ROC curve analysis showed that sFlt/PLGF had greater predictive value for preeclampsia, with a sensitivity of 98.1% and a specificity of 78.2%. Conclusions: Serum sFlt-1 level and sFlt-1/PlGF ratio have better predictive and diagnostic values, as well as better auxiliary efficiency for preeclampsia. The diagnostic efficiency of sFlt-1/PlGF ratio is better than sFlt-1 content alone.